The Effects of Task-Based Learning And Blooket on Enhancing Reading Comprehension In The Eleventh Grader - Rttanapongpinyo, Wisa; Prasansaph, Soranabordin (Journal of Dhamma for Life, 2025)
The objectives of this research were to 1) compare the English reading comprehension skills of students before and after learning through Task-based learning activities integrated with Blooket, and 2) study students’ opinions towards the task-based learning integrated with Blooket. The sample consisted of 36 Grade 11th students during the first semester of the 2024 academic year. The sample was selected by a clutter random sampling technique from a secondary school in Dusit District, under the Secondary Educational Service Area Office Bangkok Area 1. The research instruments consisted of 1) four lesson plans utilizing Task-based learning with Blooket, 2) an English reading comprehension achievement test, and 3) a questionnaire on students’ opinions towards the task-based learning with Blooket. The data were analyzed by Mean ( ), Standard deviation (S.D.), and t-test dependent. The research results showed that 1) the English reading comprehension skills of Grade 11 students after learning through Task-based learning with Blooket were significantly higher than before using Task-based learning with Blooket at the .05 level, and 2) students’ opinions towards Task-based learning with Blooket was rated at the highest level of agreement.